2019
DOI: 10.1016/j.jses.2019.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative parameters that predict postoperative patient-reported outcome measures and range of motion with anatomic and reverse total shoulder arthroplasty

Abstract: Background: Preoperative factors that most influence postoperative outcomes of both anatomic total shoulder arthroplasty (aTSA) and reverse total shoulder arthroplasty (rTSA) are unknown. The purpose of this study was to identify the preoperative parameters that significantly influence postoperative outcomes of aTSA and rTSA. Methods: The outcomes of 1089 aTSA patients and 1332 rTSA patients (mean follow-up period, 49 months) from an international registry with a single platform system were analyzed. A multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 30 publications
0
54
0
1
Order By: Relevance
“…The causes of poor functional improvement after RSA are still unclear. Regarding patient factors, age, 15 , 18 female, 15 small and large stature, 27 and high BMI 39 are reported risks for poor outcomes. High BMI was only detected as a factor associated with poor elevation in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes of poor functional improvement after RSA are still unclear. Regarding patient factors, age, 15 , 18 female, 15 small and large stature, 27 and high BMI 39 are reported risks for poor outcomes. High BMI was only detected as a factor associated with poor elevation in this study.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Most patients improve their function including shoulder elevation after surgery, but some patients show less improvement than expected. 18 Various factors have been reported that are related to the poor improvement of shoulder function after RSA including age, 15 , 18 sex, 15 patients’ stature, 27 obesity, 39 deltoid muscle volume, 43 preoperative range of motion, 14 preoperative diagnosis, 11 , 19 , 42 and glenosphere size and position. 6 , 10 , 30 , 32 , 33 …”
mentioning
confidence: 99%
“…The success of TSA as a treatment option in patients with shoulder OA is depending on many factors. [21] Objective parameters such as the improvement of range of motion and an increase of strength as well as subjective values like pain reduction are involved in patient satisfaction after surgery. [22,23] The observation that the radiographic OA signs increase with increasing patient age is in line with a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…The success of TSA as a treatment option in patients with shoulder OA is depending on many factors. 11 Objective parameters such as the improvement of range of motion and an increase of strength as well as subjective values like pain reduction are involved in patient satisfaction after surgery. 15,27 The observation that the radiographic OA signs increase with increasing patient age is in line with a previous study.…”
Section: Discussionmentioning
confidence: 99%